ANALISIS KEBERHASILAN PEMBANGUNAN MANUSIA BERDASARKAN PERATURAN DAERAH KABUPATEN BONE NOMOR 11 TAHUN 2016 TENTANG PENGARUSUTAMAAN GENDER DALAM PEMBANGUNAN DAERAH - Sugirman, Andi; Satriadi, Satriadi; Harianto, Dadang (Datuk Sulaiman Law Review (DaLRev), 2022)
This study discusses the Analysis of the Success of Human Development Based on the Regional Regulation of Bone Regency Number 11 of 2016 concerning Gender Mainstreaming in Regional Development. The main problem is how to analyze the success of gender-oriented human development based on Gender Mainstreaming (PUG) and how the Human Development Index (IPM) in Bone Regency is in regional development. What is the role of the implementation of PUG institutions in Bone Regency in resolving each gender gap? This study employs normative-empirical research methods, with qualitative research methods described descriptively and employing conceptual approaches, law, sociology of law, and comparative and legal psychology to examine legal aspects in social interactions within government and community, and serves as a support to identify and clarify the findings of non-legal materials for the purposes of research or legal writing.The results of the study show that the existence of a regional regulation that regulates PUG in regional development has proven to be able to solve gender problems and gaps, as seen from the increase in the percentage of the Gender Development Index (IPG) and the Gender Empowerment Index (IDG), It is also able to contribute to the HDI growth rate in Bone Regency, although it has not been able to shift Bone Regency's HDI ranking from 23rd out of 24 Regencies in South Sulawesi, with PUG implementation starting from every Regency, subdistrict, and village. Keywords: Awareness Gender , Development Region, Human Development